Full 3D modeling of soil structure interaction by using solid finite elements - Awla, Halmat Ahmed; Karaton, Muhammet (Academic Publication Council, 2022)
Numerical studies for considering soil-structure interaction (SSI) are widely used to provide a better understanding of the seismic behavior of structures. The outcomes of these numerical studies are strongly depending on the input parameters. Back to the literature, for modelling different types of soil, there are convenient procedures whereby a single value of the Poisson's ratio is estimated for each type of soil; however, a range limitation between 0.10 and 0.40 is possible, and then other required parameters are determined utilizing the tables of the international seismic codes and the equations of the literature. In this article, a comprehensive parametric study was carried out with the aim of evaluating influences of the Poisson's ratio on the seismic behavior of structures, and sixteen values of Poisson's ratios were interpolated between 0.11 and 0.41 in order to examine all possible trails. For achieving this goal, a 4-story steel structure was analyzed on four different soil types (soft, stiff, very dense, and rock soils) under the El Centro acceleration record. The results in terms of time history top displacement and base shears have been discussed.
Keywords: Direct method; Substructure method; Soil types; Soil-structure interaction; Solid finite elements